Paraconsistent inteligent system for autonomous mobile robot control - Torres, Germano Lambert; Torres, Cláudio Rodrigo; Abe, Jair Minoro (Revista Ciências Exatas, 2008)
This work intends to show a controller based on the evidential annotated paraconsistent logic Eτ – Paracontrol. The Paracontrol is a variation of the logic analyzer. This work also shows an autonomous mobile robot, which is named Emmy II, in order to demonstrate the Paracontrol’s new properties. As an innovation, the Paracontrol presents besides the characteristics of the previous controller (manipulation of uncertainties, contradiction and paracompleteness information), the speed control in the various robot’s actions.